Nghiên cứu về một số loại hình phương tiện biểu đạt tình thái trong câu hỏi tiếng Anh=An inverstigation into different types of modality markers in English /Võ Đại Quang;Nguyễn Thị Vân Anh. - Võ, Đại Quang .
This article is focuses on three types of modality markers in English:Syntactic structures;vocatives;modal auxiliary verbs.